Rooting biostimulants for coffea Arabica L. Cuttings - de Azevedo, Harianna Paula Alves (2020)
In the rooting process of Arabica coffee cuttings, plant hormones are used for inducing root formation. However, synthetic molecules cannot be used to form organic seedlings. The objective of this work was to evaluate the effect Cyperus haspan extract and different concentrations and types of humic substances on Arabica coffee cuttings. Arabica coffee shoots were collected, and cuttings containing at least two buds were taken. The experiment had a three-factor design, 2 (presence or absence Cyperus haspan extract) x 2 (humic or fulvic acid) x 4 (0, 10, 25 and 50 mg dm-³ concentrations). The following vegetative data were evaluated: shoot height (cm), survival, remaining leaves, leaf pairs, vigor, number of shoots,root length, area root, volume root, diameter root and fresh and dry mass were also evaluated. The enzyme activity of H+-ATPase, catalase, superoxide dismutase, alcohol dehydrogenase and esterase was also quantified. The results showed that the Arabica coffee cutting rooting rate was increased when treated with humic acid at a concentration of 10 mg dm-³ in the presence of Cyperus haspan extract. The lowest oxidative stress was observed in the 10 mg.dm-³ humic and fulvic acid treatments, regardless of the use of the extract.